2011
DOI: 10.1111/j.1365-2443.2010.01479.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analyses using a mouse cell cycle mutant identifies magoh as a novel gene involved in Cdk regulation

Abstract: Many of the genes that control cyclin-dependent kinase (Cdks) activity have been identified by genetic research using yeast mutants. Suppression analysis and synthetic enhancement analysis are two broad approaches to the identification of genetic interaction networks in yeasts. Here we show, by genetic analyses using a mammalian cell cycle mutant, that mouse magoh is involved in Cdk regulation. Magoh, a homolog of the Drosophila mago nashi gene product, is a component of the splicing-dependent exon-exon juncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…siRNA knockdown of Magoh in HeLa cells causes G2/M arrest(Kittler et al, 2007; Silver et al, 2010). Moreover, similar to our in vitro findings with MEFs and melanocyte-derived cells, Magoh siRNA treated tsFT210 and FM3A cells show reduced proliferation in culture (Inaki et al, 2011). How might Magoh impact melanoblast division?…”
Section: Discussionsupporting
confidence: 86%
“…siRNA knockdown of Magoh in HeLa cells causes G2/M arrest(Kittler et al, 2007; Silver et al, 2010). Moreover, similar to our in vitro findings with MEFs and melanocyte-derived cells, Magoh siRNA treated tsFT210 and FM3A cells show reduced proliferation in culture (Inaki et al, 2011). How might Magoh impact melanoblast division?…”
Section: Discussionsupporting
confidence: 86%
“…21 On the other hand, Magoh is involved in the regulation of mouse Cdks. 11 Totally, it is possible that RBM8A-depleted human cells in our study also have similar deficiency and G2/M arrest via their alternation. EJC serves as a platform for NMD factors and their various roles in cell cycle progression have been reported.…”
Section: Discussionmentioning
confidence: 93%
“…We found that 314 proteins were in common between the proteomes, suggesting a possible function for these proteins throughout mitosis or cytokinesis (Figure 4 and Table S3) [9]. Proteins unique to the CHO mitotic spindle proteome included known spindle components such as SEPT7 and SEPT9, which are required for stable kinetochore localization of CENP-E [48], PAF1, which regulates Histone 2B and mediates the progression of the cell cycle [49], and MAGOHB, the mago-nashi homolog, which regulates cyclin dependent kinases [50]. Proteins appearing in only the CHO midbody proteome included ECT2 and KIF4A, both of which are critical for cytokinesis completion [51], [52].…”
Section: Resultsmentioning
confidence: 99%